PENGEMBANGAN MEDIA SMART CARD JAWA UNTUK MENINGKATKAN KETERAMPILAN MENULIS PADA MATERI AKSARA JAWA LEGENA SISWA KELAS III SDN BATUKALI - Amalia, Irsa Dina; Wiranti, Dwiana Asih (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
Many elementary school students find Javanese language lessons difficult to understand because of its diversity, which is the background for this research. The aim of carrying out this research is to improve writing skills through the Javanese Legena script material for class III students at SDN Batukali through the use of Javanese smart card media. The type of research used was research and development (RD) with the ADDIE model, involving 27 grade III students at SDN Batukali as research subjects. Based on the needs analysis, it shows that students experience obstacles in observing the writing of the Javanese legena script.Â  Therefore, Javanese smart card media is designed to resemble a card equipped with instructions in the form of small numbers next to Javanese script. The results of this research prove that the validation aspect by material experts obtained a score of 87.5%, while the media validation aspect received a score of 77.5%, both of which are in the feasible category. The results of the Java smart card media trial revealed a difference between the average pretest result of 53.51 and posttest of 76.66. Effectiveness is shown through the results of the writing skills test using the paired sample test with SPSS 25, with a significance value (2-tailed) of 0.000 0.005. In conclusion, the use of Javanese smart card media has proven to be very effective in improving Javanese script writing skills in elementary school students and other equivalent educational institutions.